2012
DOI: 10.1111/j.1600-0714.2012.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of adhesion/growth‐regulatory galectin‐9 from squamous cell epithelium in head and neck carcinomas

Abstract: Galectins are potent effectors of cell adhesion and growth regulation. Their expression as comples network necessitates systematic study of each member of this family. Toward this aim, we here focus on the tandem-repeat-type galectin-9. Its presence is monitored in normal squamous epithelium of the head and neck, the surgical margin, and four types of squamous cell carcinoma. Lectin presence was detected in cells of the basal layer of the epithelium. All galectin-9-negative epithelia showed aberrant positivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…Similar to the previously discussed galectins, galectin‐9 has been linked to complex processes in tumor initiation and progression such as tumor immunity, cell adhesion, migration, and metastasis . In fact, change of a normally physiologic state into a malignant state has been associated with loss of this protein . Our results revealed that galectin‐9‐positive cells significantly decreased with the increase of malignant transformation risk.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the previously discussed galectins, galectin‐9 has been linked to complex processes in tumor initiation and progression such as tumor immunity, cell adhesion, migration, and metastasis . In fact, change of a normally physiologic state into a malignant state has been associated with loss of this protein . Our results revealed that galectin‐9‐positive cells significantly decreased with the increase of malignant transformation risk.…”
Section: Discussionsupporting
confidence: 84%
“…To date, 15 galectins have been identified in mammals, each one containing at least one conserved carbohydrate‐recognition domain that preferentially binds to β‐galactosides . Functionally polyvalent, these lectins are involved in several physiological and pathological process such as angiogenesis , apoptosis , differentiation , and metastasis . The function may differ depending on their location, once galectins can be present in the cytoplasm and move into the nucleus or can be secreted to extracellular space .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Gal-1, -3, -4, -7, -8 and -9 were produced in bacteria, purified to homogeneity, as confirmed by one-dimensional and two-dimensional gel electrophoreses, gel filtration, and mass spectrometry, and used as antigens to develop polyclonal antibodies in rabbits (3640). The resulting IgG fractions were rigorously checked for cross-reactivity among the lectin family, with systematic testing of human Gal-1, -2, -3, -4, -7, -8 and -9 by western blot analysis and enzyme-linked immunosorbent assay.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of low p53 and high Bcl-XL expression is associated with poor overall survival and disease specific survival [55, 57]. The negligible effect of HNSCC treatment on the activity of the above-mentioned genes, based on the level of cRNA, can be interpreted according to our recent results demonstrating differentiation-dependent expression of the endogenous lectin galectin-9 in normal squamous cell epithelium and in cancer [58]. Although normal squamous epithelium from noncancer patients demonstrated strictly basal cell expression, the malignant epithelium of tumours and a significant amount of histologically normal epithelium from HNSCC patients were devoid of expression of this lectin.…”
Section: Discussionmentioning
confidence: 97%